Dynamics and structure of mortality from chronic coronary artery disease among men and women in the Russian Federation in 2014-2023 - R. N. Shepel; I. V. Samorodskaya; E. P. Kakorina; O. M. Drapkina (Российский кардиологический журнал, 2024)
Aim. To assess the dynamics of non-standardized (NSMR) and standardized mortality rates (SMR) of chronic coronary artery disease (CAD), the contribution to all-cause mortality, as well as the dynamics and structure of chronic CAD among men and women in the Russian Federation in 2014-2023.Material and methods. Rosstat data on mortality in one-year age groups of patients for 2014-2023 in accordance with the Rosstat Brief Nomenclature of Death Causes. The calculations were performed using the program (certificate of state registration of the computer program dated September 30, 2016, № 201666114). The European standard (European Standard Population, 1976) was used to calculate the SMR.Results. A decrease in the SMR from chronic CAD was found in both women (2014 — 147,6 per 100 thousand population, 2023 — 126 per 100 thousand population) and men (2014 — 275 per 100 thousand population, 2023 — 221 per 100 thousand population). The NCMR differences in men and women did not exceed 5%, while the SMR from chronic CAD differed by almost 2 times due to the age disproportion (in age ≥80 years in women, there were 60% of deaths from chronic CAD, while in men — 23,6%). The proportion of chronic CAD in all-cause mortality in men was 23,9%, while in women — 23,4%. The highest values of SMR were recorded from "I25.1 Atherosclerotic heart disease" (the proportion in the chronic CAD structure in 2014 in women — 64,5%, in men — 56,8%; in 2023 — 60,4% and 51,4%, respectively). In both men and women, the SMR and the proportion of "I25.2-6,8 Other forms of chronic CAD" in the structure of SMR from chronic CAD increased (in 2014 in women — 21,5%, in men — 29,3%, in 2023 — 37% and 46%, respectively). The SMR from I25.0 and I25.9 significantly decreased, amounting to <4% in the structure of chronic CAD in both men and women in 2023.Conclusion. The obtained results indicate problems with defining individual forms of chronic CAD as the underlying cause of death, which complicates understanding the death causes. It is necessary to consider creating uniform guidelines for the Russian Federation, where the classification of chronic CAD according to ICD-10 would be adapted to the clinical terminology and the most probable clinical variants, as well as the main principles of morphological classification. Typification of coding approaches will serve to improve the quality of analysis of chronic CAD mortality statistics data and subsequent adoption of targeted management decisions.